Character of the Atheist Propaganda in Lithuania in 1975 to 1988 - Streikus, Arūnas (Genocidas ir rezistencija, 2003)
In reference to archival documentation of the Soviet institutions, official press publications and bibliographical indexes, the article reviews trends of the atheist propaganda in Lithuania during the last decades of the Soviet regime, and also attempts to point out its particularity in comparison to the atheistic indoctrination performed in Lithuania earlier. It was tried to identify the impact to the atheist propaganda in Lithuania by both, common trends of political development for the entire Soviet Union (after the death of Leonid Brezhnev, started was the course for restoration of the ideological discipline), and by specific local conditions (strengthening movement of believers' rights, commemoration of the dates important in history of Christianity in Lithuania).Analysis of atheist publications in the periodical press, and quantity of the non-periodical publications gives presumption that after the conditional decrease at the end of the Leonid Brezhnev rule the atheist propaganda was again intensified in 1983. Meanwhile, thematic analysis of the atheist literature gives presumption that the main features of atheist activities in Lithuania in 1975 to 1988 were such: most focus was made on the atheist indoctrination of youth; evidently increased the amounts of information about the non-Christian religions; coordination of the atheist and the so-called international education; attempts to give the atheist propaganda a more steady scientific foundation; large amounts of publications which analyzed the role of Christianity in Lithuanian history.
Keywords: Soviet regime; Soviet religious policy; atheism; propaganda; Catholic church